PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 4 PADANG - Intan, Nadya; R.,, Syahrul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT The purpose of the research are (1) to describe exsplanatory text writing skills of VIII grade students SMP Negeri 4 Padang before applying discovery learning model whitin serial piscture media, (2) to describe exsplanatory text writing skills of VIII grade students SMP Negeri 4 Padang after applying discovery learning model whitin serial piscture media, and (3) to analize effect of discovery learning model whitin serial piscture media to exsplanatory text writing skills of VIII grade students SMP Negeri 4 Padang. Based on the data analize the application of discovery learning model whitin serial piscture media affects the exsplanatory text writing skills of  VIII grade students SMP Negeri 4 Padang. Kata kunci: pengaruh, discovery learning¸ media gambar berseri, menulis teks eksplanasi